Investigating the Effect of Annealing on the Properties of Cu2SnS3 Thin Films Using Spin Coating - Rahaman, Sabina; K. B., Jagannatha; Tanjavur, Thyagaraj; Lakshmisagar, . (Current Approaches in Science and Technology Research Vol. 14, 2021)
Due of its electrical and optical properties, Copper Tin Sulphide is a worthy material for thin film hetero-junction solar cells. It's a ternary direct band gap p-type material with significant thin-film solar cell potential. Its constituents are innocuous, abundant in the earth crust and affordable. The goal of this paper is to define the deposition of CTS thin films on soda-lime glass substrates using a jejune sol-gel spin coating process at various temperatures. The effect of annealing temperatures on the development and properties of the films is investigated utilizing appropriate characterization methods to investigate their optical, structural, and morphological aspects. CTS has a cubic structure, according to XRD analysis. SEM analysis revealed that the facet for solar cells is suitable. After annealing, the energy bandgaps of the films decrease from 1.61eV to 1.45eV, according to optical quantifications. For semiconducting materials used as an absorber layer in thin film solar cells, such energy gap magnitudes are optimal.